2006
DOI: 10.1111/j.1600-0749.2006.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skin response to ultraviolet exposure and skin color type

Abstract: Sun exposure is responsible for detrimental damage ranging from sunburn to photoaging and skin cancer. This damage is likely to be influenced by constitutive pigmentation. The relationship between ultraviolet (UV) sensitivity and skin color type was analyzed on 42 ex vivo skin samples objectively classified from light to dark skin, based on their values of individual typology angle (ITA) determined by colorimetric parameters. The biologically efficient dose (BED) was determined for each sample by quantifying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 57 publications
3
104
1
5
Order By: Relevance
“…No published study investigating vitamin D status in HIV has evaluated skin pigmentation in lieu of race. It has long been known that blacks have a higher prevalence of vitamin D deficiency due to increased skin pigmentation which decreases the production of vitamin D 3 in the skin [51]. However, this study suggests that skin pigmentation may be a better method of identifying people who are the most at risk.…”
Section: Discussionmentioning
confidence: 77%
“…No published study investigating vitamin D status in HIV has evaluated skin pigmentation in lieu of race. It has long been known that blacks have a higher prevalence of vitamin D deficiency due to increased skin pigmentation which decreases the production of vitamin D 3 in the skin [51]. However, this study suggests that skin pigmentation may be a better method of identifying people who are the most at risk.…”
Section: Discussionmentioning
confidence: 77%
“…Supporting this suggestion, experimental studies have shown that the amount of UVR-related DNA damage did not differ among those with darker skin phototype compared to whites (33). The difference in disease incidence may be partially explained from the observations that among non-whites, the UVR-related DNA damage may have a higher rate of repair (33) and/or may be restricted to the upper layers of skin (34). …”
Section: Discussionmentioning
confidence: 99%
“…It was calculated based on luminosity (L*) and blue-yellow (b*) colorimetry measurements of the skin (Del Bino, Sok, Bessac, & Bernerd, 2006). Participants were categorized into one of six skin color categories previously established by the cosmetic and dermatology industries (very light, light, intermediate, tan, brown, and dark) (COLIPA, 2007;Del Bino et al, 2006). This objective method of categorizing skin color based on ITA has been effectively used in previous bruise research (Scafide, Sheridan, Campbell, Deleon, & Hayat, 2013) and within the dermatologic and cosmetic industries (Uhoda, Pierard-Franchimont, Petit, & Pierard, 2003).…”
Section: Data Collectionmentioning
confidence: 99%
“…Using a handheld Konica Minolta ® CM-700d spectrophotometer, skin color was assessed using the Individual Typology Angle (ITA). It was calculated based on luminosity (L*) and blue-yellow (b*) colorimetry measurements of the skin (Del Bino, Sok, Bessac, & Bernerd, 2006). Participants were categorized into one of six skin color categories previously established by the cosmetic and dermatology industries (very light, light, intermediate, tan, brown, and dark) (COLIPA, 2007;Del Bino et al, 2006).…”
Section: Data Collectionmentioning
confidence: 99%